Assessment of genetic variability for quantitative characters in rice (Oryza sativa L.) under post flood situation in sali - Pathak, Dalibha; Kalita, Umesh Ch. (ORYZA-An International Journal of Rice, 2021)
Sixteen genotypes of rice (including one check) were evaluated on 18 quantitative traits during sali (August), 2018 in a randomized block design with three replications at Instruction cum Research Farm, Department of Plant Breeding and Genetics, Assam Agricultural University, Jorhat to study the nature and magnitude of variability, heritability and genetic advance under delayed sown condition. The analysis of variance for 18 quantitative traits revealed the presence of significant differences for grain yield and its component characters.The highest genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) was observed for chaffs per panicle followed by grains per panicle, spikelet sterility (%), spikelets per panicle, grain yield (kg/ha). A high heritability coupled with high genetic advance was observed for plant height (cm), spikelets per panicle, spikelet sterility (%), chaffs per panicle, grains per panicle, grain yield (g/hill), grain yield (kg/ha), biological yield (kg/ha), straw weight (kg/ha) and harvest index (%) indicating that selection might beeffective for improvement of these characters under delayed sown condition with low input. From the findings of this investigation, one genotype viz., Gandhari emerged as the outstanding genotype which yielded 4170 kg/haand could be directly used for cultivation in delayed sown situation with low inputs. Some other promising genotypes that yielded higher than the check Manoharsali under delayed sown condition were JR 29, JR 16, Basundhara and JR 60 and could be utilized as potential parental material in the hybridization programmes designed to develop suitable rice varieties for delayed sown situation.